2022
DOI: 10.1039/d2ee00109h
|View full text |Cite
|
Sign up to set email alerts
|

Defects and performance of Si PV modules in the field – an analysis

Abstract: Photovoltaic installations will likely become one of the major power sources in the 21st century and we need photovoltaic modules to operate reliably. In this review, we explore what is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 93 publications
0
18
0
Order By: Relevance
“…Recent trends in global climate policy stimulated a dramatic growth of photovoltaic (PV) deployment with an expected level of tens of terawatts worldwide to be reached in one to two decades. , This enormous growth serves as a locomotive for the development of associate technologies in the production, monitoring, and recycling of PV modules. In particular, the expected TW scale of PV installations requires efficient high-throughput procedures for automated characterization of the status of deployed PV modules, their integrity, performance, and state of degradation. The most promising technologies for the high-throughput characterization include different imaging techniques, such as thermography, electroluminescence (EL), , and photoluminescence (PL) imaging, , which can be realized on automated moving/flying platforms and provide essential information on the module performance and type/population of defects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent trends in global climate policy stimulated a dramatic growth of photovoltaic (PV) deployment with an expected level of tens of terawatts worldwide to be reached in one to two decades. , This enormous growth serves as a locomotive for the development of associate technologies in the production, monitoring, and recycling of PV modules. In particular, the expected TW scale of PV installations requires efficient high-throughput procedures for automated characterization of the status of deployed PV modules, their integrity, performance, and state of degradation. The most promising technologies for the high-throughput characterization include different imaging techniques, such as thermography, electroluminescence (EL), , and photoluminescence (PL) imaging, , which can be realized on automated moving/flying platforms and provide essential information on the module performance and type/population of defects.…”
Section: Introductionmentioning
confidence: 99%
“…Field data on the status of PV plants over many years of operation, which became available recently due to improved imaging techniques, indicated that the degradation state and the general performance of the Si PV modules depend not only on the quality of Si cells and metal interconnects but also on the bill of materials (BOM) of polymer components of PV modules. In particular, transparent encapsulants and polymer backsheets (BSs) were shown to be performance relevant. , The recognition of the important role of polymer components, in particular transparent encapsulants and BSs, in the life cycle of Si PV modules stimulated the development of new approaches for field characterization of relevant polymers, mostly based on vibrational spectroscopies and fluorescence imaging of PV module encapsulants. , …”
Section: Introductionmentioning
confidence: 99%
“…At the same time, inverters collect and provide numerous monitoring data, including general performance indicators and ground impedance (GI), the latter characterizing cumulative insulation resistance of the modules serviced by each specific inverter. The safe and continuous operation of inverters is a prerequisite for the successful implementation of PV energy conversion, and this task is regulated by numerous international and national standards covering inverter operation, performance measurements, safety, installation mode, and so forth 1–3 …”
Section: Introductionmentioning
confidence: 99%
“…The safe and continuous operation of inverters is a prerequisite for the successful implementation of PV energy conversion, and this task is regulated by numerous international and national standards covering inverter operation, performance measurements, safety, installation mode, and so forth. [1][2][3] While inverters are supposed to operate safely and efficiently, their operation depends on the performance and insulation state of each PV modules connected to it. Numerous standards and limitations are in place to ensure safe operation of the inverters, in particular, a minimal threshold insulation resistance (or GI) of 1 MΩ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation